Blepharoplasty: historical aspects, terminology, and modern ideas - A.D. Kazantsev; E.P. Kazantseva; I.B. Alekseev (РМЖ "Клиническая офтальмология")
A.D. Kazantsev, E.P. Kazantseva, I.B. Alekseev Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation Visual contact is one of the important aspects of non-verbal communication. The look of every person is unique, it emphasizes individuality and represents what is happening in the inside and emotional experience. When we look in the eyes, we gain our first impression of an interlocutor and his/her psych evaluation. Irreversible changes of periorbital tissues of the upper face occur with aging. They result in the functional changes and visible cosmetic defects, thereby negatively affecting psychological social status and provoking eyelid discomfort. Patients refer to specialists (plastic or ocular surgeons) to address these age-related issues. Blepharoplasty is a popular, effective, and safe surgical procedure to reconstruct periorbital soft tissues. The history of blepharoplasty began in the 10th century when a Persian scientist Avicenna described a technique of removing the excessive overhanging skin of the upper lids. Later on, blepharoplasty goes through a long way of development, evolution, and practice. Blepharoplasty is no less important today, being one of the most common esthetic procedures of plastic surgery worldwide. Modern, highly effective diagnostic tools and professional medical equipment allow for an accurate prediction of surgical outcome, thereby emphasizing the importance of the conception "desired changes — realistic expectations". This paper reviews the historic aspects and current views on blepharoplasty, and professional terminology used by plastic and ocular surgeons specializing in esthetic eyelid surgery. Keywords: blepharoplasty, history of blepharoplasty, plastic surgery, eye surgery, periorbital area, professional terminology, current ideas, preoperative planning, reconstruction of eyelid soft tissues. For citation: Kazantsev A.D., Kazantseva E.P., Alekseev I.B. Blepharoplasty: historical aspects, terminology, and modern ideas. Russian Journal of Clinical Ophthalmology. 2022;22(2):127–131 (in Russ.). DOI: 10.32364/2311-7729-2022-22-2-127-131.